Clinical Features, Short-Term Mortality, and Prognostic Risk Factors of Septic Patients Admitted to Internal Medicine Units: Results of an Italian Multicenter Prospective Study. Issue 4 (January 2016) - Mazzone, Antonino; Dentali, Francesco; La Regina, Micaela; Foglia, Emanuela; Gambacorta, Maurizia; Garagiola, Elisabetta; Bonardi, Giorgio; Clerici, Pierangelo; Concia, Ercole; Colombo, Fabrizio; Campanini, Mauro
Abstract : Abstract: Only a few studies provided data on the clinical history of sepsis within internal Medicine units. The aim of the study was to assess the short-term mortality and to evaluate the prognostic risk factors in a large cohort of septic patients treated in internal medicine units. Thirty-one internal medicine units participated to the study. Within each participating unit, all admitted patients were screened for the presence of sepsis. A total of 533 patients were included; 78 patients (14.6%, 95%CI 11.9, 18.0%) died during hospitalization; mortality rate was 5.5% (95% CI 3.1, 9.6%) in patients with nonsevere sepsis and 20.1% (95%CI 16.2, 28.8%) in patients with severe sepsis or septic shock. Severe sepsis or septic shock (OR 4.41, 95%CI 1.93, 10.05), immune system weakening (OR 2.10, 95%CI 1.12, 3.94), active solid cancer (OR 2.14, 95% CI 1.16, 3.94), and age (OR 1.03 per year, 95% CI 1.01, 1.06) were significantly associated with an increased mortality risk, whereas blood culture positive for Escherichia coli was significantly associated with a reduced mortality risk (OR 0.46, 95%CI 0.24, 0.88). In-hospital mortality of septic patients treated in internal medicine units appeared similar to the mortality rate obtained in recent studies conducted in the ICU setting.